How does service description contribute to peer-to-peer service satisfaction? Consumer clout matters - Zhu, L.; Lin, Y.; Cheng, Mingming; Cen, J. (2025)
Purpose: This paper aims to decode how service descriptions contribute to consumer satisfaction in the peer-to-peer service context and how consumer clout interferes with such influence. Based on the expectation–confirmation theory, the authors hypothesise that lowered expectations induced by modest service descriptions strengthen the performance-satisfaction link. In addition, the authors posit that consumer clout influences the moderation effect of service descriptions. Design/methodology/approach: The paper is an empirical study using data of Airbnb, a representative peer-to-peer service platform. The data includes all listings in San Francisco, where Airbnb is headquartered. A total of 5,567 listing descriptions with 241,791 review comments were analysed after removing non-English texts. The host descriptions and guest reviews are analysed with the Linguistic Inquiry and Word Count and Google Cloud. The Tobit and ordered logistic models were used for hypothesis testing. Findings: Guests are more likely to give higher ratings when they feel positive about the accommodation services. Such effect is stronger for lower guest expectations induced by modest host descriptions, as lower expectations are more likely to generate positive surprise disconfirmation. The previous relationship is moderated by guest clout, as guests high in clout pay less attention to host descriptions and are less likely to be surprised. Originality/value: The paper investigates the joint influence of service descriptions and consumer reviews on peer-to-peer service satisfaction. The paper conducted entity-level sentiment analysis to examine opinions expressed towards specific types of entities. The paper also explored how consumer clout moderates the relationship, a boundary condition that previous studies have not explored.